Pengaruh Sistem Pengendalian Internal, Komitmen Organisasi Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa - Footlia Iyona; Mahdalena Mahdalena; Ronald S. Badu (Jurnal Mirai Management, 2023)
This study aims to determine the effect of the internal control system, organizational commitment and the use of information technology on the accountability of managing village funds in the District of South Bulango, Bone Bolango Regency. The type of research used is the quantitative method, the source of the data used in this research is primary data obtained directly from respondents in the District of South Bulango. The total population in this study is 103 people using purposive sampling technique, namely the technique of determining the sample with certain criteria. The results showed that partially the internal control system variable (X1) had a positive and significant effect on village fund management accountability (Y), organizational commitment (X2) had a positive and significant effect on village fund management accountability (Y), and information technology utilization (X3). positive and significant effect on village fund management accountability (Y). Keywords: Internal Control System, Organizational Commitment, Utilization of Information Technology and Village Fund Management Accountability